Pengaruh Motivasi, Komunikasi, Gaya Kepemimpinan Dan Kompensasi Melalui Kepuasan Kerja Karyawan Pada Kantor Pengawasan Dan Pelayanan Bea & Cukai Jenis Bea Cukai Bontang. - muhammad junaid kamaruddin; gazali gazali (Economy Deposit Journal (E-DJ), 2021)
This research investigates and analyzes the impact of motivation, communication, leadership style, and compensation variables on work satisfaction. The populations in this study were employees at the Customs and Excise Office of Bontang C Type of Customs and Excise Office, which numbered 113 persons. Saturated samples were used for sampling. Furthermore, there are two methodologies used: descriptive and explanatory. The information obtained was from quantitative data that was statistically analyzed. The data in this study was analyzed utilizing statistical analysis, namely SEM-Structural Equation Modeling with AMOS-22 tools. The results showed that motivation contributed to the increase in job satisfaction. Communication and leadership do not directly affect job satisfaction. Compensation has a significant effect on job satisfaction.